The Influence Of Education Through Video Media On Knowledge Of How To Use Insulin Pen In Diabetes Mellitus Patients At Pesanggrahan Hospital, Selatan Jakarta - Muniasih, Rantri; Dinaryanti, Ratna Sari (Jurnal EduHealth, 2023)
Diabetes is a series of chronic metabolic disorders caused by the pancreas not producing enough insulin, causing both absolute and relative insulin deficiency, resulting in increased glucose concentration in the blood. Pharmacological handling of insulin includes administering an insulin pen that is used correctly. This research aims to determine the effect of education through video media on knowledge of how to use insulin pens in diabetes patients. This research method uses a Quasi-Experimental design with a research design of "one group pre-test and post-test design. The population in this study were DM patients at Pesanggrahan Regional Hospital, with a total sample of 18 DM patients. The instrument in this study uses a questionnaire to measure the level of knowledge about insulin pens and a barcode containing a video of insulin pen use—a statistical test using T Dependent. This study's results significantly influence knowledge of how to use an insulin pen before and after providing education with a p-value of 0.000 (p-value < 0.05). It is hoped that the results of this research can become a basis for nursing services to provide education to diabetes mellitus patients regarding knowledge of how to use insulin pens using videos.